2004
DOI: 10.1093/bja/aeh219
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative intravenous crystalloid infusion on postoperative nausea and vomiting after gynaecological laparoscopy: comparison of 30 and 10 ml kg−1

Abstract: I.V. administration of CSL 30 ml kg(-1) to healthy women undergoing day-case gynaecological laparoscopy reduced the incidence of vomiting, nausea and anti-emetic use when compared with CSL 10 ml kg(-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 40 publications
(32 reference statements)
3
65
1
1
Order By: Relevance
“…We (28) and others (29) have shown that supplemental perioperative fluid administration reduces the risk of postoperative nausea and vomiting. For example, patients given a loading dose of 15 mL/kg crystalloid experienced less nausea and vomiting after gynecologic surgery than those given 2 mL/kg (28).…”
Section: Discussionmentioning
confidence: 89%
“…We (28) and others (29) have shown that supplemental perioperative fluid administration reduces the risk of postoperative nausea and vomiting. For example, patients given a loading dose of 15 mL/kg crystalloid experienced less nausea and vomiting after gynecologic surgery than those given 2 mL/kg (28).…”
Section: Discussionmentioning
confidence: 89%
“…90 Using a rapid infusion of 30 mL·kg -1 of iv isotonic solution, the severity of nausea and the incidence of vomiting were reduced, in comparison to 10 mL·kg -1 volume loading in ambulatory laparoscopic gynecology. 91 However, dizziness, thirst, and opioid consumption were not different between groups in that trial. Knowledge of these factors warrants specific fluid management strategies in ambulatory surgery to minimize the likelihood of delayed discharge and to maximize patient satisfaction.…”
Section: Factors Delaying Discharge Following Ambulatory Surgerymentioning
confidence: 72%
“…18,19 Induction of anesthesia in which systolic pressures decrease 35% is associated with a higher incidence of PONV than is induction in which systolic pressures decrease less. 17 Preliminary reports 19,20 of more aggressive preoperative hydration suggest that this intervention can diminish PONV, but the mechanism by which the reduction occurs is unclear.…”
Section: Angela Smith Collins Rn Dsn Acns Bc Ccnsmentioning
confidence: 99%